تقدير تعويض الضرر في حوادث السير وإشكالاته في التأمين الإسلامي: دراسة تحليلية في ضوء مقاصد الشريعة - نجار،,يحيى عبد الله عايش (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The research aims to study two main issues related to estimation of the compensation paid by Islamic insurance due to traffic or road accidents. The research examined the compensation provided by the insurance company from the Maqasid of Shari'a perspective. This was carried in five chapters: research plan and general structure, the concept of compensation, Shari'a acceptability, types and its Maqasid of Shari'a, the responsibility and rulings pertaining to the damage in Islamic insurance, compensation of road accident and its Shari'a basis, time, methodology of estimation and impact on the company of Islamic insurance in the Gaza Strip (Palestine) in the light of Maqasid of Shari'a of the insured and the insurance company and finally concerns in estimating the compensation by the obligor. The researcher relied on the inductive approach to follow up on these issues. The researcher also relied on interviews and questionnaires The research found that the reasons behind the dispute between the affected party and the insured on the amount of compensation is due to non-availability of a committee and experts who are non-biased to the insurance company or the affected party by damage. It is due to long legal procedures in case of disputes casued by the absence of a clear law which fixes the time frame for closing the compensation cases in the civil courts. The reason behind the agreement of the insurer with the compensation, despite their reservation on the suitability of the amount, would be due to economic reasons and non-awareness of procedures and requirements of estimation operations. The researcher provided a general recommendation, the most important ones are offering insurance products like compensation in line with Shari'a rulings on blood-money and an insurance product which serves social segments which are disadvantaged and not covered by compensation such as involving the elderly. In short, the research looked at issues which are uniquely and direcly related to compensation and governance in Islamic insurance companies.